Research on the development path of China’s cross-border e-commerce industry under the COVID epidemic - Kučera Jiří; Zhang Yan (SHS Web of Conferences, 2023)
The COVID-19 epidemic in 2020 has swept the world, bringing great challenges to Chinese cross-border e-commerce industry, as well as opportunities for development. According to my country's economic survey in the first and second quarters of 2020, the COVID-19 epidemic has caused a sharp drop in the transaction volume of Chinese foreign trade industry, while the crossborder e-commerce industry has grown against the trend. Starting from the characteristics of Chinese cross-border e-commerce industry, this article analyzes the impact of the COVID-19 epidemic on Chinase cross-border e-commerce industry, mainly in the obstruction of logistics and the impact on the global supply chain. Taking Ali International Station as a case analysis, through the formulation of support policies for sellers, investment in digital trade and other measures to help e-commerce sellers to tide over the difficulties, and then put forward suggestions on path selection for Chinese cross-border e-commerce industry to cope with the COVID-19 epidemic.